A systematic review of the nutritional status of adults experiencing homelessness. (July 2022) - Huang, C.; Foster, H.; Paudyal, V.; Ward, M.; Lowrie, R.
Abstract: Objectives: To identify, appraise, and describe studies focussing on the nutritional characteristics of people experiencing homelessness (PEH). Study design: Systematic (narrative) review. Methods: We identified full-text studies of any design and in the English language of adults (≥18 years) fulfilling the European Typology criteria for homelessness, based in community or hospital settings, and which report nutritional measures. Five electronic databases, 13 grey literature sources, reference lists, and forward citations were searched. Data on study characteristics and nutrition measures were collected and synthesised narratively. Risk of bias was assessed using relevant checklists for each study type. Results: A total of 1130 studies were identified and retrieved. After screening, six studies were included for review: three cross-sectional studies; two case–control studies; and one randomised control trial, involving a total of 1561 participants from various settings including shelters, drop-in centres, hospitals, and hostels. All included studies were from high-income countries. Studies reported a range of nutrition measures including anthropometry (e.g., body mass index (BMI)), serum micronutrients and biomarkers, and dietary intake. Between 33.3% and 68.3% of participants were overweight or obese; 3.5%–17% were underweight; and low blood levels of iron, folate, vitamins C, D, and B12, and haemoglobin were prevalent. PEH consumed high amounts of dietary fats and alcohol, and low amounts of fruits and vegetables compared with national guidelines and housed individuals. There was moderate to high risk of selection and measurement bias and confounding in included studies. Conclusions: A majority of PEH are within unhealthy BMI ranges and are deficient in serum micronutrients and nutritional biomarkers. Studies using large data sets that examine multiple aspects of nutrition are needed to describe the nutritional characteristics of PEH. Registration: This systematic review is based on a prespecified protocol registered with the International Prospective Register of Systematic Reviews (PROSPERO CRD42021218900).